Dance-movement therapy as psychological support for women during the war - Milyutina, Kateryna; Bybka, Anna (Psychological Prospects Journal, 2025)
Purpose. Ttheoretical justification and experimental determination of the impact of dance-movement therapy (DMT) on the psycho-emotional state of middle-aged women during the war. The study is aimed at studying the effectiveness of DMT in reducing stress, anxiety and improving emotional stability in this age group, as well as developing practical recommendations for the use of DMT.Methods. The study was conducted at the Center for Psychological Support and Development. 60 middle-aged women (from 35 to 50 years old) participated in the study: 30 women - experimental group, 30 women - control group. The following psychodiagnostic methods were used in the study: Methodology "Self-assessment of mental states" (according to G. Eysenck), DEPS Depression Scale, Beck Anxiety Scale. Women in the experimental group underwent an 8-week dance-movement therapy course, during which regular assessments of their psycho-emotional state were conducted. Women in the control group underwent only diagnostic work, no correction was performed.Results. There was a decrease in the indicators of anxiety, aggressiveness, frustration, and depression in women in the experimental group. The conducted one-factor analysis of variance confirmed the presence of statistically significant differences between the groups of respondents and the positive effect of the dance-movement therapy course on the manifestations of depression, aggressiveness, and frustration. Respondents in the control group, who received only social assistance during this time, did not demonstrate significant changes in their psycho-emotional state.Conclusions. Dance-movement therapy had a positive effect on reducing the level of anxiety, depression, and aggression in women with average indicators of these states. No positive effect of the implemented dance-movement therapy program on the rigidity of the respondents was recorded. Patients with high levels of anxiety and depression did not experience significant improvement under the influence of dance-movement therapy. The study confirms the effectiveness of DMT in comprehensive socio-psychological support of the mental state of women during the war, but does not have proven effectiveness in the therapy of high levels of anxiety and depression.